Class-acquired influenza is more severe than non-class-acquired influenza: a survey for multi-school teachers - Jin, Ruoqi; Zhao, Heng; Ma, Ying; Wu, Shunjun; Meng, Wanting; Li, Jing; Cai, Zhigui; Yang, Ling; Li, Chenyao; Song, Liqiang (Frontiers in Public Health, 2025)
BackgroundDuring the influenza season, teachers have a higher infection rate of influenza than the general population. However, there has been no study on the clinical characteristics of this specific influenza in infection type—“class-acquired influenza,” which means teachers acquire influenza infection from exposure to a substantial quantity of influenza virus aerosols in enclosed classrooms by teaching activities in a short period of time.MethodsIn this study, teachers who had suffered from influenza during the 2024–2025 Seasonal Influenza from 12 schools in Xi'an, a city in northern China, were retrospectively collected through a questionnaire. They were divided into a class-acquired influenza group and a non-class-acquired influenza group, and then compared the clinical features and effects between these two groups.ResultsClass-acquired cases showed higher incidence of symptoms, such as fever, cough, malaise, abdominal pain and diarrhea, and showed greater severity of symptoms like dry throat, runny nose and sputum. The class-acquired influenza group had longer recovery time [7.0 (5.0, 14.0) vs. 6.5 (5.0, 10.0) days, p = 0.003], and required more medical visits (69.9% vs. 52.3%, p = 0.004), medication (74.7% vs. 62.4%, p = 0.035), and sick leave (47.9% vs. 28.4%, p < 0.001). Incubation period (onset) showed no difference (p = 0.245).ConclusionClass-acquired influenza is a specific type in teachers. Compared to non-class-acquired influenza, it involves worse symptoms, longer duration, higher healthcare needs, and more absenteeism, likely related to the unique working conditions and environment. Therefore, during the influenza season, schools and teachers should focus on rational prevention, early diagnosis and medication.